The Relationship Of Knowledge And Attitude Of Public Mothers With Early Feeding Of MPASI In The Work Area - Dewi Sartika Hutabarat; Novita Sari Dewi; Cindy Hidayat; Sri Muliana Putri Bakara; Yanti Nirmala; Hotmadeli Siregar (Poltekkes Kemenkes Palembang, 2022)
Background: The World Health Organization or the World Health Organization declares that breast milk is the right food and is suitable for the growth and development of infants throughout the world. However, giving baby complementary foods before reaching the age of 6 months and over will have a very detrimental effect on the baby. Exclusive breastfeeding for infants (< 6 months) contributes greatly to the reduction in infant mortality. On the other hand, giving additional food too early will increase the risk of developing both infectious and non-infectious diseases for the baby. Purpose: This study aims to determine how closely the mother's knowledge and attitudes are with the provision of early MP-ASI in the Kedai Sianam Health Center Work Area, Batu Bara Regency. Methods: This study uses a quantitative approach with the type of observational research with a cross-sectional design where the independent and dependent variables are measured at the same time. The population used is all mothers who have a baby of 6 months. The number of samples based on the sample formula is 32 people. In this study, sampling was done by simple random sampling or by simple random sampling where all members of the population had the opportunity to be selected as samples. Results: The relationship between the mother's level of knowledge about complementary feeding and the provision of complementary feeding in early months in the Kedai Sianam 33 Health Center Work Area, Batu Bara Regency in 2022 with a number of 32 respondents, there is a significant relationship with a p value of 0.001 where the majority of respondents who have poor knowledge give Complementary foods for babies before 6 months. .